Pemanfaatan Bubuk Kulit Buah Mangifera indica L. sebagai Pupuk Tanaman Brassica juncea L. di Green House Pendidikan Biologi UKI Tahun 2021 - Hutri Tambunan; Yovita Harmiatun; Fajar Adinugraha (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the benefits of the fruit rind of Mangifera indica L. var arum manis (Mangga Arum Manis) as organic fertilizer on the growth of Brassica juncea L., to know the process of making the skin of the fruit of Mangifera indica L. var arum manis into organic fertilizer powder, as well as to determine the average growth of Brassica juncea L. (mustard greens) when using Mangifera indica L. var arum manis rind fertilizer, inorganic NPK fertilizer, or using only tap water. This type of research is an experimental study, namely the effect of giving powdered waste skin of Mangifera indica L. var arum manis inorganic NPK fertilizer, and giving ordinary tap water as fertilizer on the growth of Brassica juncea L. plants by using RAK (Randomized Block Design) one factor. The rind of the mango fruit can be made into fertilizer in the form of powder by drying in the sun which is then crushed to form a powder. Manganese rind powder can be used as organic fertilizer for the growth of mustard plants. The treatment of mustard plants with manganese rind powder fertilizer 50 g/L, resulted in mustard height and stalk length of mustard greens up to DAP (days after planting) 42, and also produced wider mustard leaves up to DAP 35, which was superior to the treatment of mustard plants with NPK fertilizer of 20 g/L and treat the mustard plant with water. The treatment of mustard plants with 20 g/L NPK fertilizer resulted in more mustard leaves up to 42 DAP, and wider mustard leaves, but only at 42 DAP, compared to the treatment of mustard plants with 50 g/L manganese rind powder fertilizer, and treatment of mustard greens with water